Aspects of physical aging, mechanical rejuvenation, and thermal annealing in a new copolyester. Issue 8 (10th November 2014) - Cugini, Angela V.; Lesser, Alan J.
<x xml:space="preserve">Abstract</x> Long‐term effects of physical aging and mechanical rejuvenation are monitored through dynamic mechanical properties of an amorphous glassy polymer. These phenomena are investigated through dynamic mechanical testing that evaluates in situ the evolution of the storage modulus with time during annealing and physical aging. Comparisons are made on samples with different thermal histories and mechanical treatment (rejuvenation). The polymer characterized in this contribution is a new commercially available copolyester under the tradename of Tritan™. The results are discussed in context to different aging rates obtained from the various thermal and mechanical treatments; both measurements of aging rates are compared. POLYM. ENG. SCI., 55:1941–1950, 2015. © 2014 Society of Plastics Engineers